Sistematização de um Programa de Capacitação ao Professor do Aluno Surdo1 - Tenor, Ana Claudia [UNESP]; Deliberato, Débora [UNESP] (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2015)
The aim of this study was to systematize actions for training teachers who work with deaf students through the mediation of the speech therapist. The participants were a father, a mother and two teachers of deaf students who are included students. The study was conducted in three stages: during the first stage parents and teachers were interviewed. After that, an adapted protocol was used and observations in the classroom without interventions were performed. Protocol data, observations, and interviews were triangulated and the content was analyzed, which consisted of thematic units' classification. Based on the themes identified in the first stage, a training program was designed for teachers of deaf students, which was developed during the second phase of the research. Simultaneously to the training group, the researcher conducted observations and interventions in the classrooms of the participating teachers. Data from the training meetings, observations records and intervention shootings were triangulated and the content was analyzed, identifying the thematic units. In the third stage, the followup of teachers in their classrooms was carried out and their opinions about the training program were identified through interviews. Interview data were analyzed and classified into categories and subcategories for analysis. This training program enabled the teachers to understand the specific language of their deaf students, the need for resources and adaptation strategies, as well as the need to empower the families to support the use of communication.

O objetivo desse estudo foi sistematizar ações para a capacitação do professor do aluno surdo por meio da mediação do fonoaudiólogo. Participaram um pai, uma mãe e duas professoras de alunos surdos incluídos. O estudo foi realizado em três etapas: na primeira etapa os pais e professores foram entrevistados, em seguida foi utilizado um protocolo adaptado e foram realizadas observações em sala de aula sem intervenção. Os dados do protocolo, das observações e das entrevistas foram triangulados e em seguida realizou-se análise de conteúdo, que consistiu em classificação de unidades temáticas. A partir das temáticas identificadas na primeira etapa foi elaborado um programa de capacitação ao professor do aluno surdo que foi desenvolvido na segunda etapa da pesquisa. Concomitante ao grupo de capacitação, a pesquisadora realizou observações e intervenções na sala de aula dos professores. Os dados dos encontros de capacitação, os registros das observações e filmagens das intervenções foram triangulados, em seguida realizou-se análise de conteúdo identificando-se unidades temáticas. Na terceira etapa, foi feito o acompanhamento dos professores em sala de aula e identificada as suas opiniões a respeito do programa de capacitação por meio de entrevistas. Os dados das entrevistas foram analisados e classificados em categorias e subcategorias de análise. O programa de capacitação possibilitou aos professores compreenderem as especificidades linguísticas do aluno surdo, a necessidade de adaptação de recursos e estratégias e apontou a necessidade de capacitação das famílias para o uso de suporte a comunicação.
Systematization of a Training Program for Teachers of Deaf Student
Keywords: Special Education; Inclusion; Training; Teacher; Deaf Student; Educação Especial; Inclusão; Capacitação; Professor; Aluno surdo